Do Cryopreserved Mesenchymal Stromal Cells Display Impaired Immunomodulatory and Therapeutic Properties?. (September 2014) - Moll, Guido; Alm, Jessica J.; Davies, Lindsay C.; von Bahr, Lena; Heldring, Nina; Stenbeck‐Funke, Lillemor; Hamad, Osama A.; Hinsch, Robin; Ignatowicz, Lech; Locke, Matthew; Lönnies, Helena; Lambris, John D.; et al.
Abstract We have recently reported that therapeutic mesenchymal stromal cells (MSCs) have low engraftment and trigger the instant blood mediated inflammatory reaction (IBMIR) after systemic delivery to patients, resulting in compromised cell function. In order to optimize the product, we compared the immunomodulatory, blood regulatory, and therapeutic properties of freeze‐thawed and freshly harvested cells. We found that freeze‐thawed MSCs, as opposed to cells harvested from continuous cultures, have impaired immunomodulatory and blood regulatory properties. Freeze‐thawed MSCs demonstrated reduced responsiveness to proinflammatory stimuli, an impaired production of anti‐inflammatory mediators, increased triggering of the IBMIR, and a strong activation of the complement cascade compared to fresh cells. This resulted in twice the efficiency in lysis of thawed MSCs after 1 hour of serum exposure. We found a 50% and 80% reduction in viable cells with freshly detached as opposed to thawed in vitro cells, indicating a small benefit for fresh cells. In evaluation of clinical response, we report a trend that fresh cells, and cells of low passage, demonstrate improved clinical outcome. Patients treated with freshly harvested cells in low passage had a 100% response rate, twice the response rate of 50% observed in a comparable group of patients treated with freeze‐thawed cells at higher passage. We conclude that cryobanked MSCs have reduced immunomodulatory and blood regulatory properties directly after thawing, resulting in faster complement‐mediated elimination after blood exposure. These changes seem to be paired by differences in therapeutic efficacy in treatment of immune ailments after hematopoietic stem cell transplantation. Stem Cells2014;32:2430–2442